University: Toward “Beyond the Horizon” Strategy - Kh. G. Tkhagapsoev (Высшее образование в России)
The article shows that the entrenched orientation of higher education towards the demands of the labor market requires rethinking and adjustment, since in modern conditions it does not guarantee the effectiveness of university’s activities and the ability to meet the challenges of the future. The real basis and guarantee of the university’s success is now the “synchronization” of its development strategy with the historical and epistemological trends in the development of knowledge, its functions and forms of being. In this context, the role and place of techno-science at university and university processes – research, design, and educational – is becoming especially important. It is argued that the current trends in the development of knowledge and science bring to life (and have already provoked) a new “projective-personal” paradigm of education. It is not focused on mastering the maximum academic knowledge (as it has been so far), but on individualizing the trainee’s educational trajectory and mastering the methods of synthesizing knowledge and project activities.